2018
DOI: 10.2166/washdev.2018.080
|View full text |Cite
|
Sign up to set email alerts
|

Microbial contamination of non-household drinking water sources: a systematic review

Abstract: Drinking water in non-household settings (e.g. schools, health care facilities (HCFs), restaurants, and mass gatherings) that is free of contamination is important for human health, especially in settings with vulnerable populations who are more at risk from the use of unsafe drinking water, such as immunocompromised patients in HCFs and children at school. Few studies have characterized water quality in non-household settings. We examined the quality of drinking water in non-household settings using studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Separately, it should be noted that one of the schools (KAZ200084) additionally had a toilet not on the school premises. On the one hand, the presence of a such a spare and independent model points to the level of school improvement, but on the other hand, such locations need more serious monitoring, primarily to ensure the safety of students in every sense [ 30 ]. Nowadays, very often toilets, including those in urban areas, do not meet these requirements [ 29 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Separately, it should be noted that one of the schools (KAZ200084) additionally had a toilet not on the school premises. On the one hand, the presence of a such a spare and independent model points to the level of school improvement, but on the other hand, such locations need more serious monitoring, primarily to ensure the safety of students in every sense [ 30 ]. Nowadays, very often toilets, including those in urban areas, do not meet these requirements [ 29 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The third study [49] is a systematic review that evaluated the quality (Escherichia coli, thermotolerant coliforms, and total coliforms) of drinking water in nonhousehold settings. The review found that drinking water in nonhousehold settings is often noncompliant with health-based standards as defined by the World Health Organization.…”
Section: Water and Sanitationmentioning
confidence: 99%
“…According to the recent BIS slandered reports [15] and literatures [28][29] the microbial contamination is the main reason for water borne diseases like diarrhea. Likewise, as per…”
Section: Screening For Bacterial Contaminationmentioning
confidence: 99%
“…This concludes that the remaining samples are free from bacteria, and also we can say that the water samples (GN1, GN2, GN11 and GN18) which are collected from hospitals were free from bacterial contamination, due to the presence of less turbidity inbecause those samples which were collected from hospitals have less turbidity this is one of the reason for absence of bacteria in those samples. It is interesting to find that samples like GN3 and the reports it is anticipated that in 2015, an estimated 1.3 million people lost their lives from diarrheal diseases and among them 499,000 were children, younger than five years old [28]. So, Microbial contamination, which is reducing water quality is linked to causing inflammation, anemia, stunting and it's becoming the matter of concern [29][30].…”
Section: Screening For Bacterial Contaminationmentioning
confidence: 99%